Evaluation of modafinil as a perpetrator of metabolic drug–drug interactions using a model informed cocktail reaction phenotyping trial protocol. (10th January 2018) - Rowland, Angela; van Dyk, Madelé; Warncken, David; Mangoni, Arduino A.; Sorich, Michael J.; Rowland, Andrew
Abstract : Aim: To evaluate the capacity for modafinil to be a perpetrator of metabolic drug–drug interactions by altering cytochrome P450 activity following a single dose and dosing to steady state. Methods: A single centre, open label, single sequence cocktail drug interaction trial. On days 0, 2 and 8 participants were administered an oral drug cocktail comprising 100 mg caffeine, 30 mg dextromethorphan, 25 mg losartan, 1 mg midazolam and 20 mg enteric‐coated omeprazole. Timed blood samples were collected prior to and for up to 6 h post cocktail dosing. Between days 2 and 8 participants orally self‐administered 200 mg modafinil each morning. Results: Following a single 200 mg dose of modafinil mean (± 95% CI) AUC ratios for caffeine, dextromethorphan, losartan, midazolam and omeprazole were 0.95 (± 0.08), 1.01 (± 0.35), 0.97 (± 0.10), 0.98 (± 0.10) and 1.36 (± 0.06), respectively. Following dosing of modafinil to steady state (200 mg for 7 days), AUC ratios for caffeine, dextromethorphan, losartan, midazolam and omeprazole were 0.90 (± 0.16), 0.79 (± 0.09), 0.98 (± 0.11), 0.66 (± 0.12) and 1.90 (± 0.53), respectively. Conclusions: These data support consideration of the risk of clinically relevant metabolic drug–drug interactions perpetrated by modafinil when this drug is co‐administered with drugs that are primarily cleared by CYP2C19 (single modafinil dose or steady state modafinil dosing) or CYP3A4 (steady state modafinil dosing only) catalysed metabolic pathways.